1974
DOI: 10.1353/sls.1974.0005
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Deletion in American Sign Language

Abstract: The American Sign Language of the deaf (ASL) has a level of structure which is analogous to phonology. The natural basis for both lexical description and analysis of variation is the articulatory dynamics of the hands and body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
381
0
52

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(437 citation statements)
references
References 3 publications
4
381
0
52
Order By: Relevance
“…The latter result confirms that the facilitation found in English derives from the phonological similarities of the picture names rather than pictorial or semantic differences in the materials. Having been replicated in multiple studies (Kuipers & La Heij, 2009;Meyer & Damian, 2007;Navarrete & Costa, 2005; but see Jescheniak, Oppermann, Hantsch, Wagner, Madebach, & Schriefers, 2009) Linguistic analyses on sign articulation in natural languages have revealed four major phonological parameters that are probably universal: handshape, location of the sign relative to the body, movement of the hand, and orientation (Battison, 1978;Sandler & Lollio-Martin, 2006;Stokoe, Casterline, & Croneberg, 1965). These parameters vary cross-linguistically in number and typology, and are combined according to language-specific and language universal constraints giving rise to the whole inventory of signs in a given language.…”
Section: Experiments 1: Phonologically Related Signsmentioning
confidence: 99%
“…The latter result confirms that the facilitation found in English derives from the phonological similarities of the picture names rather than pictorial or semantic differences in the materials. Having been replicated in multiple studies (Kuipers & La Heij, 2009;Meyer & Damian, 2007;Navarrete & Costa, 2005; but see Jescheniak, Oppermann, Hantsch, Wagner, Madebach, & Schriefers, 2009) Linguistic analyses on sign articulation in natural languages have revealed four major phonological parameters that are probably universal: handshape, location of the sign relative to the body, movement of the hand, and orientation (Battison, 1978;Sandler & Lollio-Martin, 2006;Stokoe, Casterline, & Croneberg, 1965). These parameters vary cross-linguistically in number and typology, and are combined according to language-specific and language universal constraints giving rise to the whole inventory of signs in a given language.…”
Section: Experiments 1: Phonologically Related Signsmentioning
confidence: 99%
“…Stokoe 1960;Battison 1978) have described four primary phonological parameters that differentiate signs from one another: handshape, movement, orientation and location. Much of the earlier literature focused on ASL, although research since then has shown that many of these hold for other sign languages as well.…”
Section: Phonological Constraints On Native Signsmentioning
confidence: 99%
“…-When both hands are moving, the Symmetry Condition (Battison 1978) specifies that both hands must have the same mirrored location, the same handshape, and the same movement (either simultaneous or alternating). -The Dominance Condition (Battison 1978) specifies that if they do not share the same handshape, then the non-dominant hand remains stationary and is "acted on" by the dominant hand.…”
Section: Phonological Constraints On Native Signsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mãos são geralmente descritas na literatura sobre as línguas de sinais por meio dos termos ativo ou passivo e dominante ou não-dominante (BATTISON, 1978). Designa-se como ativa a mão que apresenta movimento e passiva a que fica estacionada, servindo de ponto de articulação para a ativa.…”
unclassified